Multi-Electron Charge Carriers for Next-Generation Flow Batteries - Peake, Catherine (2022)
The necessity to meet the ever-growing demand for energy while simultaneously reducing carbon emissions, requires a shift towards renewable sources of electricity. The intermittent nature of these sources has fuelled a demand for low-cost and reliable grid-scale energy storage. Redox flow batteries (RFBs) offer a promising solution due to their long cycle life and scalability. However, widespread commercial uptake of RFBs requires a reduction in cost and increase in energy density compared to the archetypal all-vanadium system. Increasing the volumetric energy density of RFBs requires the development of charge carriers with high solubility and the ability to undergo multi-electron redox processes. The rich electrochemistry of polyoxometalates (POMs) and fullerenes make them particularly promising charge carriers for high energy density batteries. We demonstrate how functionalisation of these species can enhance their solubility and redox properties to further increase the energy density of RFBs. Furthermore, we focus on their application in nonaqueous electrolytes where the wide window of electrochemical stability allows for high voltages to be achieved. This thesis encompasses the design, synthesis, and characterisation of functionalised multi-electron charge carriers, and investigation of their performance in nonaqueous RFBs. Chapter 2 discusses the theory behind electrochemical energy storage devices and the assessment metrics used for quantifying the performance of RFBs. We highlight the challenges of chemical compatibility of battery components with nonaqueous solvents and present best practice for testing of nonaqueous electrolytes in laboratory-scale RFBs. In chapter 3 we seek to enhance the solubility of POMs in nonaqueous solvent through organic-inorganic hybridisation. We describe the synthesis and electrochemical analysis of the hybridised POM, TBA3[PW11O39(SiC6H5)2O], PW11-SiPh. Organofunctionalisation of the phosphotungstate Keggin-type POM with phenyl siloxane groups, increases its saturation concentration in acetonitrile by two orders of magnitude over that of the parent compound. The stability of PW11-SiPh is investigated in several symmetric RFBs, and the system demonstrates high coulombic efficiency (98%), voltage efficiency (89%), and energy efficiency (87%) during redox cycling. We show that capacity fade due to oxidation state imbalance and asymmetric membrane crossover can be counteracted by reduction or redistribution of electrolytes respectively. However, when cycling within a wide potential window such that PW11-SiPh is reduced by four electrons per molecule, its stability appears to be diminished and rapid capacity fade is observed. In chapter 4 we explore the application of PW11-SiPh as charge carrier in the negative electrolyte of an asymmetric RFB. The battery uses the nitroxide radical 2,2,6,6-tetramethylpiperidinyloxyl (TEMPO) as the charge carrier in the positive electrolyte allowing for a larger cell voltage and theoretical energy density to be achieved compared to the symmetric system with PW11-SiPh alone. Stable cycling was achieved for >400 hours with cell voltage of 1.6 V and coulombic efficiency of 95% (when PW11-SiPh was reduced by three electrons upon charge). However, capacity fade due to membrane crossover was realised with this battery, as indicted by the presence of PW11-SiPh in the positive electrolyte. Furthermore, the stability of the RFB was dramatically reduced when PW11-SiPh was reduced by four electrons, indicating significant degradation of the hybrid POM under these conditions. In chapter 5, the multi-electron redox process of fullerene and the positive redox potential of ferrocene were coupled to generate a bifunctional charge carrier termed C60Fc. A symmetric C60Fc RFB exhibited an impressive coulombic efficiency (96%), voltage efficiency (77%), and energy efficiency (74%) over 100 cycles (150 hours). However, capacity fade of 0.3% per cycle was observed and ascribed to charge carrier degradation. A series of C60Fc charge carriers were synthesised in which the organic functionality surrounding the pyrrolidine ring linking the fullerene and ferrocene groups was modified. C60Fc charge carriers featuring a hexyl chain on the pyrrolidine linker group were found to have increased solubility in dichlorobenzene and therefore increased theoretical energy density in the resulting RFB. An unexpected consequence of the organic modification to C60Fc was its increased propensity to transport across the separator. RFBs with the hexyl substituent demonstrated significant asymmetric membrane crossover. The detrimental effect of asymmetric crossover on capacity retention was found to be preventable by polarity switching.